Pengaruh Atribut Produk, Harga, dan Citra Merek terhadap Keputusan Pembelian Kopi Bubuk Instan Merek Indocafe di Kota Surabaya - Eko Priyanto; Qelbi Ghefira; Indra Tjahaja Amir (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This research is motivated by an increase in the amount of coffee consumption of the Indonesian population. The large level of public consumption in consuming coffee causes coffee producers to compete fiercely to be more innovative in developing their products to seize market share. The high level of competition in the increasingly diverse instant ground coffee beverage industry will affect the level of consumer purchasing decisions. The purpose of this study was to analyze the effect of product attribute (X1), price (X2), and brand image (X3) on purchasing decisions (Y) of Indocafe brand instant coffee in Surabaya. The sample was determined using purposive sampling method. Data was collected by distributing questionnaires. The data analysis method used is Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that product attributes, price, and brand image had a positive and significant effect on purchasing decisions.